Purwarupa Sistem Peringatan Dini Kebakaran Berbasis IoT dengan ESP32-CAM dan Notifikasi Telegram - Andreas Jurdil Widiarsa (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Warehouses that store cardboard boxes carry a high fire risk because the stored material is highly flammable and a fire can spread quickly once it starts. Monitoring in many such warehouses still relies on periodic human checks, so the appearance of smoke or flame is often noticed late, which can increase the resulting loss. This study designs and builds an Internet of Things (IoT)-based prototype that detects fire indications, issues an early warning, and performs an initial suppression action in a cardboard box warehouse. The prototype uses an MQ-2 sensor to sense smoke and a flame sensor to sense fire directly, both connected to an ESP32-CAM acting as the main controller. Once a hazard is detected, the ESP32-CAM switches on a buzzer, drives a relay that activates a mini water pump, captures a photo through its onboard OV2640 camera, and forwards the photo together with a warning message to the user through a Telegram bot. Functional testing shows that the prototype detects smoke and flame accurately, triggers the buzzer and pump in under one second, and delivers the Telegram notification with photo within three to five seconds. These results indicate that the prototype can support faster fire detection and a quicker initial response in cardboard box warehouses.